Host Adaptation and Evolutionary Analysis of Zaire ebolavirus: Insights From Codon Usage Based Investigations - Luo, Wen; Roy, Ayan; Guo, Fucheng; Irwin, David M.; Shen, Xuejuan; Pan, Junbin; Shen, Yongyi (Frontiers in Microbiology, 2020)
Ebola virus (EBOV) has caused several outbreaks as the consequence of spillover events from zoonotic sources and has resulted in huge death tolls. In spite of considerable progress, a thorough know-how regarding EBOV adaption in various host species and detailed information about the potential reservoirs of EBOV still remains obscure. The present study was executed to examine the patterns of codon usage and its associated influence in the adaptation of EBOV to potential hosts that dwell in Africa, the origin of the viral outbreaks. Correspondence analysis revealed that the codon usage signature in EBOV is a complex interplay of factors including compositional bias and natural selection, with the latter having a more pronounced impact. Low codon usage bias in EBOV indicates a flexibility of the viruses in adapting to diverse range of hosts with different codon usage architectures. EBOV adaptation in potential hosts, as estimated by codon adaptation index (CAI) and relative codon deoptimization index (RCDI), revealed that the viruses were relatively better adapted to African primates than other mammals examined, which might account for the high fatality rate of primates owing to EBOV infection. Bats have been speculated as natural reservoirs of EBOV. In the present analysis it was interesting to note that EBOV displayed lower degrees of adaptation, as estimated by CAI and RCDI, with bats in comparison to the primate hosts. Lower degrees of adaption might contribute to long-term co-existence and circulation of the viral pathogens in bat populations. Codon usage patterns of EBOV isolates associated with different outbreaks varied significantly, with discrete patterns between the West and Central African isolates. Additional evolutionary analyses indicated that the West African Epidemic began with an initial spillover infection and there was more than one population of EBOV circulating in the natural reservoir in the Democratic Republic of the Congo. The present study yields valuable information regarding the possible circulation of EBOV in various African mammals.